Investigation of the food safety of lamb meat obtained in ecologically unfavorable territories - Apsalikova, Zukhra; Amirkhanov, Kumarbek; Gaptar, Svetlana; Mukanova, Alima; Yevlampiyeva, Yelena; Kassymov, Samat; Brait, Yulia; Spanova, Assem; Lipikhina, Aleksandra; Apsalikov, Kazbek (Frontiers in Sustainable Food Systems, 2024)
This article presents data on the ecological situation of agricultural territories where small cattle are raised, namely, the exposure dose rate, radioecological measurements of radon concentration in residential buildings and in social buildings, the density of alpha and beta particle flux. The article presents studies of raw meat grown in ecologically unfavorable territories for the content of heavy metals (Pb, Cd, As, Hg) and radionuclides Cs-137 and Sr-90, and also considers ways to reduce the content of heavy metals and radionuclides in meat when exposed to heat treatment. A decrease in the levels of toxic elements and radionuclides in meat has been established during its heat treatment. Therefore, the level of lead in meat decreased from 0.29 mg/kg to 0.12 mg/kg, cadmium from 0.03 mg/kg to 0.013 mg/kg, arsenic from 0.066 mg/kg to 0.055 mg/kg, respectively. Prolonged heat treatment reduced the level of Cs-137 and Sr-90 radionuclides from 3.564 Bq/kg to 1.075 Bq/kg and from 0.02 Bq/kg to 0.012 Bq/kg, respectively. The greatest decrease in the levels of toxicity and radionuclides is observed during prolonged heat treatment, cooking or quenching. Meat samples were taken on the territory of the Abai district adjacent to the former Semipalatinsk Nuclear Test Site (Semey, Kazakhstan).